O direito internacional dos refugiados e o ordenamento Jurídico brasileiro: análise da efetividade da proteção nacional - Soares, Carina de Oliveira (2019)
The international institute of the refuge is extremely important because it aims to ensure broad protection to people who find themselves in very vulnerable situation. Brazilian government undertook the international commitment to protect refugees, ratifying the 1951 Convention and 1967 Protocol, related to the Statute of Refugees, and has adopted a specific law disciplining it, Law 9.474/97, which is considered by United Nations (UN) as a parameter to the adoption of a uniform legislation among the countries of South America. Brazil is often recognized as "host country" for refugees, endowed with a well-structured domestic law on the subject. Because of that, Brazil earns a favorable image of its role in refugee protection. The objective of this research is to analyze the effectiveness of national protection, making sure that, in fact, the instrument norms are being applied properly and that these people received in Brazil effectively enjoy the rights that were established in the 1951 Convention, the Constitution of 1988 and Law 9.474/97. To do that, a dogmatic study about the theme will be developed, using the deductive method, observing and interpreting the rules of domestic law and international law. Will be further developed a theoretical/philosophical methodology, from the bibliographic study of doctrines seeking to learn and to develop what the legal theorists say about the subject in examination and, finally, it is going to be done a sociological, pragmatic/realistic analysis about the theme, with a research of the situation of refugees in Brazil since the time of their arrival in the national territory and when they formalize the request of refuge to the Federal Police, until the moment of integration into Brazilian society, and a case law analysis, looking how the judiciary is positioning itself in the protection of the rights of refugees. Related to that, the real facts are going to be observed, comparing them to the ideal model idealized by the doctrine. Although there is a considerable effort to ensure broad protection to refugees, much remains to be done to this protection to occur effectively, particularly regarding the "right to request refuge" and the "right to not be deported" (principle of non-refoulement) and also, regarding the local integration and assistance to refugees, guaranteeing access to public health, education, work and housing as assured to Brazilians, and the establishment of national specific policies to meet the special needs of refugees.